PFG-NMR studies of ATP diffusion in PEG-DA hydrogels and aqueous solutions of PEG-DA polymers - Majer, Günter; Southan, Alexander (Diffusion Fundamentals, 2017)
Adenosine triphosphate (ATP) is the major carrier of chemical energy in cells. The diffusion of ATP in hydrogels, which have a structural resemblance to the natural extracellular matrix, is therefore of great importance to understand many biological processes. In continuation of our recent studies of ATP diffusion in poly(ethylene glycol) diacrylate (PEG-DA) hydrogels by pulsed field gradient nuclear magnetic resonance (PFG-NMR), we present precise diffusion measurements of ATP in aqueous solutions of PEG-DA polymers, which are not cross-linked to a three-dimensional network. The dependence of the ATP diffusion on the polymer volume fraction in the hydrogels, φ, was found to be consistent with the predictions of a modified obstruction model or the free volume theory in combination with the sieving behavior of the polymer chains. The present measurements of ATP diffusion in aqueous solutions of the polymers revealed that the diffusion coefficient is determined by φ only, regardless of whether the polymers are cross-linked or not. These results seem to be inconsistent with the free volume model, according to which voids are formed by a statistical redistribution of surrounding molecules, which is expected to occur more frequently in the case of not cross-linked polymers. The present results indicate that ATP diffusion takes place only in the aqueous regions of the systems, with the volume fraction of the polymers, including a solvating water layer, being blocked for the ATP molecules. The solvating water layer increases the effective volume of the polymers by 66%. This modified obstruction model is most appropriate to correctly describe the ATP diffusion in PEG-DA hydrogels.